Argonautica : Book IV - Apollonius, Rhodius; Hunter, R. L. (Richard L.) (Cambridge : Cambridge University Press, 2015)
Apollonius' epic, the Argonautica, is not just a masterpiece of Hellenistic poetry drawing on the entire tradition of previous Greek literature, but was enormously influential on Latin epic, especially Virgil's Aeneid. Book IV tells the story of the Argonauts' return to Greece with the Golden Fleece, their nightmarish trips through the uncharted rivers of central Europe and the desert wastes of North Africa, the terrible killing of Medea's brother, and the anguish of the young girl which foreshadows her bloody future. This is the first modern commentary in English. Problems of syntax and language are fully explained, and there is a sophisticated discussion of the poem as literature. It will be useful for advanced undergraduates and graduate students studying Greek poetry, as well as of interest to scholars.
Acknowledgements -- References and abbreviations -- Map -- Introduction -- 1 Apollonius and the Argonautica -- 2 The fourth book -- 3 The return itinerary -- 4 Odyssey and Argonautica -- 5 Apollonius and Callimachus -- 6 The hexameter -- 7 The text -- Sigla -- Commentary.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Jason -- (Mythological character) -- Poetry; Medea, -- consort of Aegeus, King of Athens (Mythological character) -- Poetry; Argonauts (Greek mythology) -- Poetry; Epic poetry, Greek